2022
DOI: 10.3390/agronomy12123058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulp Pigmentation Intensity on Consumer Acceptance of New Blood Mandarins: A Cross-Cultural Study in Spain and Italy

Abstract: One of the current objectives of different citrus breeding programmes is obtaining new pigmented mandarins. This study investigates to what extent consumer preferences, expectations and purchase intention are affected by the appearance of new mandarins, specifically pulp pigmentation intensity. Four hundred consumers from both Italy and Spain (800 in all) participated in the study. In each country, half were informed about the healthy properties of the anthocyanins responsible for red pulp colouration, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…As the specific literature on this matter for pomegranates is lacking, all three lists of options (barriers, drivers, and contexts) were designed based on the previously existing literature for other specific fruits or for fruit as a generic group [23][24][25][26][27], as well as on previous author experiences. Then a group of eight consumers participated in a session to generate the final list of terms to be included in the questionnaire.…”
Section: Barriers Drivers and Contexts For Pomegranate Consumptionmentioning
confidence: 99%
“…As the specific literature on this matter for pomegranates is lacking, all three lists of options (barriers, drivers, and contexts) were designed based on the previously existing literature for other specific fruits or for fruit as a generic group [23][24][25][26][27], as well as on previous author experiences. Then a group of eight consumers participated in a session to generate the final list of terms to be included in the questionnaire.…”
Section: Barriers Drivers and Contexts For Pomegranate Consumptionmentioning
confidence: 99%
“…Three manuscripts that were published in this Special Issue were related to citrus fruits such as mandarin, pigmented mandarins, and lemon [6][7][8]. The communication related to mandarins was focused on late-season cultivars ('Afourer', 'Tango', and 'Orri') of mandarins grown in Spain, because they represent an important economic value due to their high production out of season.…”
Section: Introductionmentioning
confidence: 99%
“…The 'Orri' cultivar was found to be 18% higher in sugar concentration, while 'Tango' mandarins cultivated on two different rootstocks presented 28% more phenols than mandarins from an FA rootstock did. The other study, which is about the acceptance of new blood mandarins, used 800 consumers from Spain and Italy, with and without information about the health properties of the anthocyanins that are responsible for red pulp coloration [7]. Giménez-Sanchis et al [7] reported relevant results on consumer behavior in different countries regarding pigmented mandarins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation